Effects of pinealectomy and melatonin application on Serum Melatonin, Nesfatin-1 and ghrelin levels - Sönmez, Saadet; Menevşe, Esma; Baltacı, Saltuk Buğra; Ünal, Ömer; Moğulkoç, Rasim; Baltacı, Abdulkerim Kasım (Pera Publishing Services, 2023)
Objective: In this study, it was aimed to investigate the relationship between the pineal gland and ghrelin and nesfatin-1 hormones in rats. Methods: A total of 36 male rats were used in the study, and the animals were divided into 4 groups. Group 1, Control; Group 2, Pinealectomy (Px); Group 3, Px+Melatonin; Group 4 Melatonin. After the end of the experimental applications, melatonin, ghrelin and nesfatin-1 levels (ELISA) were determined in the blood samples taken from the animals. Results: While pinealectomy resulted in suppression of melatonin levels, melatonin supplementation led to a significant increase in blood melatonin levels (p<0.01). Melatonin supplementation suppressed ghrelin levels, while pinealectomy increased ghrelin levels (P<0.01). On the other hand, Nesfatin-1 levels, which increased with melatonin support, were significantly suppressed by pinealectomy (p<0.01). Conclusion: The findings of the study draw attention to an important relationship between the endocrine activity of the pineal gland and the hormones ghrelin and nesfatin-1, which play a critical role in nutrition. Consequently, administration of melatonin inhibits ghrelin but increases nesfatin-1.
Keywords: Pinealectomy; Melatonin; Nutrition; Nesfatin-1; Ghrelin; Rat